Perintah Menjaga Kedaulatan dan Kesiapsiagaan Militer dalam Al-Qur’an: Tinjauan Qs. Al-Baqarah 190 dan Qs. Al-Anfal 60: Penelitian - Lembayung Aurandyta (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Maintaining state sovereignty and increasing vigilance in the field of defense and security are crucial aspects in maintaining the integrity and safety of the Unitary State of the Republic of Indonesia (NKRI). State sovereignty includes external, internal, and territorial aspects that must be protected from various threats, both from other countries and non-military threats such as immigration violations. Efforts to maintain sovereignty are carried out through natural resource management, strengthening military defense, geopolitical diplomacy, and implementing an effective defense management system. Vigilance in the field of defense and security also involves increasing interstate cooperation, border surveillance, and strengthening public awareness and participation in the universal people’s defense system. With a holistic approach involving the government, military and society, Indonesia can face geopolitical challenges and maintain national stability in a sustainable manner.